Studi Deskriptif Mengenai Frekuensi Menonton Televisi dan Main Game Elektronik pada Anak di Semarang - Desiningrum, Dinie Ratri; Prihatsanti, Unika (Jurnal Psikologi: PITUTUR, 2011)
Not  all  mass  media  content  beneficial  to audiences.  Children  are  the  most  vulnerable group of viewers with the negative impact from television  and  technological  advances  of  the internet and video games. This study aims to capture  the  data  in  the  form  frequency  of watching  television  and  playing  electronic games on children in Semarang.The spread of datas were done by using two questionnaires,  namely  the  frequency  of watching  television  and  playing  electronic games.  Sampling  technique  was  used  in incidental  technique.  The  research  method used  was  quantitative  and  the  results  were analyzed with descriptive statistics. The  study  found  that  most  children  in Semarang  watching  television  and  playing electronic games for more than 2 (two) hours per  day,  while  the  government  recommends consumption of televisions and other electronic audiovisual media is a maximum of two hours each day, under parental guidance. This study is  one  fact  which  indicates  that  the  alert  of television and electronic games has not been noticed by parents, then it is further expected that  research  about  the  negative  impact  of television and electronic games.